THE DEVELOPMENT OF 'CHAVABOT' AS A LEARNING MEDIA THAT CAN FACILITATE STUDENTS CRITICAL THINKING IN EARTHQUAKES AND MITIGATION TOPIC - Ilma Nabila Zulfa Rabbany, - (2023)
Critical thinking skills are the main competency in learning (Permendikbud, 2013). Meanwhile, in the 2018 PISA (Program for International Student Assessment) which involves high-level thinking skills that can directly review critical thinking skills, Indonesia is ranked 73 out of 78 countries. One of the factors that can affect critical thinking skill is the use of media in learning which is very potential to build critical thinking skills and problem solving. Therefore, this study aims to develop a website-based chatbot as a learning media to facilitate student critical thinking in earthquake and mitigation topic. This research uses the development method with the ADDIE model, consist of analysis, design, development, implementation, and evaluation. The analysis stage divided into analysis of needs, characteristics, and topic. Then, in the design stage consist of flowchart and storyboard making. In the development stage, the learning media developed based on design output. In the implementation stage, the learning media tested to the students and teacher. The last is the evaluation stage, which includes the calculation of percentage data gathered from students and science teachers and the data validation by experts calculated using Aiken's Variable formula. Expert judgment results got a high value of 0.81 with the criteria of high validity. The questionnaire results from teacher and students shows different value, 94% from teachers which indicates very good and 66% from students which categorize acceptable. These findings collectively indicate the feasibility of using chatbot based learning media in the earthquakes and mitigation topic to facilitates students critical thinking.